Evaluating the effect of R-Baclofen and LP-211 on autistic behavior of the BTBR and Fmr1-KO mouse models - Sharghi, Shirin; Flunkert, Stefanie; Daurer, Magdalena; Rabl, Roland; Chagnaud, Boris Philippe; Leopoldo, Marcello; Lacivita, Enza; Hutter-Paier, Birgit; Prokesch, Manuela (Frontiers in Neuroscience, 2023)
Introduction Autism spectrum disorder (ASD) is a persistent neurodevelopmental condition characterized by two core behavioral symptoms: impaired social communication and interaction, as well as stereotypic, repetitive behavior. No distinct cause of ASD is known so far; however, excitatory/inhibitory imbalance and a disturbed serotoninergic transmission have been identified as prominent candidates responsible for ASD etiology. Methods The GABAB receptor agonist R-Baclofen and the selective agonist for the 5HT7 serotonin receptor LP-211 have been reported to correct social deficits and repetitive behaviors in mouse models of ASD. To evaluate the efficacy of these compounds in more details, we treated BTBR T+ Itpr3tf/J and B6.129P2-Fmr1tm1Cgr/J mice acutely with R-Baclofen or LP-211 and evaluated the behavior of animals in a series of tests. Results BTBR mice showed motor deficits, elevated anxiety, and highly repetitive behavior of self-grooming. Fmr1-KO mice exhibited decreased anxiety and hyperactivity. Additionally, Fmr1-KO mice’s ultrasonic vocalizations were impaired suggesting a reduced social interest and communication of this strain. Acute LP-211 administration did not affect the behavioral abnormalities observed in BTBR mice but improved repetitive behavior in Fmr1-KO mice and showed a trend to change anxiety of this strain. Acute R-Baclofen treatment improved repetitive behavior only in Fmr1-KO mice. Conclusion Our results add value to the current available data on these mouse models and the respective compounds. Yet, additional studies are needed to further test R-Baclofen and LP-211 as potential treatments for ASD therapy.